REVIEWING THE IMPLICATIONS OF THE LIVING LAW AS AN EXPANSION OF THE LEGALITY PRINCIPLE IN THE CRIMINAL CODE - Arifin, Khofifah Karalita; Primadianti, Helena (Sriwijaya Crimen and Legal Studies, 2023)
The reforms made to the Criminal Code are an achievement that must be appreciated by all Indonesian people, considering that the current Criminal Code is a legacy from the Dutch Government, so it contained therein is oriented towards Western values. Meanwhile, the Criminal Code, which the legislature of Indonesia has created, contains values following the Indonesian Nation. However, legislators' decision to include living law in the Criminal Code has brought several implications for developing criminal law in Indonesia because Indonesian criminal law also adheres to the principle of legality. The type of this research is socio-legal studies. The legal materials are collected using literature studies with the statute and conceptual approaches. Furthermore, the data processing technique has been collected using the deductive method. This article was written using a qualitative analysis method. This study aims to determine the implications of applying living law as a basis for punishment as regulated in Article 2, paragraph 1 of the new Criminal Code. The results of this study, it is known that sentence based on living law will have the impact on legal uncertainty, the duality of customary law, and requires law enforcement officers who are understand regarding the law which lives in where he is in charge because the state carries out its enforcement through the criminal justice system. The recommendation based on this research is to respect the living law by protecting the existence of indigenous people through formal arrangements in regulation forms.